Separation of organic components from crystalline silicon solar cells by supercritical fluid technology - Zachmann, Nils (My University, 2020)
Photovoltaic solar cells are a safe, efficient, reliable, and non-polluting sustainable alternative to fossil-fuel based energy source. However, decommission of solar modules become gradually an environmental issue themselves. Untreated disposal of the end-of-life modules provokes enormous environmental pollution by the enhancement of leaching of hazardous constituents plus the loss of valuable raw materials. Hence, efficient sustainable and feasible recycling of spent photovoltaic modules becomes crucial to fulfil their sustainability purpose. The biggest challenge in the recycling of the spent modules is associated with the complete removal of the organic compounds from the solar cell. The current available waste photovoltaic module recycling procedures rely either on high temperature pyrolysis, leaching agents or a combination of both. Although, pyrolysis provides the successful delamination of the encapsulant of the solar cell and the separation of the glass in environmental perspective, it is not the most sustainable solution. First of all the demand in energy during the pyrolysis process is rather high. In addition, greenhouse gases such as carbon dioxide, carbon monoxide and hydrogen fluoride are produced during the process and lead to environmental pollution. Thus, a more sustainable and simultaneous economically feasible technique for the separation of the solar cell from the encapsulation and the glass layer has to be developed. Supercritical fluid technology is proposed to be a sustainable approach as a replacement of incineration or pyrolysis methods. In this work the effects of supercritical carbon dioxide (scCO2) with and without a co-solvent on organic separation from crystalline silicon solar cell samples were investigated. Apart from pure scCO2, the solvent power combination of scCO2+DMSO and scCO2+Ethyl lactate at various pressure conditions were tested. The analysis of the FTIR-spectra of the exhaust gas as well as SEM images of the samples are leading to the conclusion that the combination of scCO2 and DMSO partly dissolves the organic layerr from the cell. The results were compared with those of the common incineration techniques on the same type. For this, FTIR-spectra from previous as well as new experiments were used to determine the exhaust gas emission of incineration system depending of temperature and high temperature reactor design. Acetic acid, carbon dioxide, carbon monoxide and hydrogen fluoride were detected in the exhaust gas.
Keywords: Photovoltaic; c-Si solar cell; Recycling; Supercritical scCO2; Incineration; Separation; EVA; Backsheet; FTIR; SEM